Pengembangan Bahan Ajar Berbasis Android Materi Prinsip Mekanika dalam Renang Bagi Mahasiswa Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi - Antonius Prasetyo Hadi; Ahmad Ilham Habibi (IKIP Budi Utomo Malang, 2023)
The purpose of this study was to produce a product development in the form of an android application that can be used to support learning the principles of mechanics in swimming for students of the Physical Health and Recreation Education Study Program IKIP Budi Utomo Malang, in order to increase students' cognitive knowledge in the field of biomechanics in swimming. The sample used was 60 students from class of 2022 taking swimming courses in the 2022/2023 academic year. the instrument used was a questionnaire for media experts, swimming learning experts, and developed media users, the development steps carried out were (1) compiling a text on biomechanics in swimming (2) developing an android application according to the material developed in the android application format. Based on the assessment of media experts and material experts as well as the results of field trials, the product developed is feasible to be used as a medium for students of the physical health and recreation education study program in swimming learning on the principle of mechanics in swimming.